TNFRSF11A-Associated Dysosteosclerosis: A Report of the Second Case and Characterization of the Phenotypic Spectrum - Xue, Jing-yi; Wang, Zheng; Shinagawa, Satoshi; Ohashi, Hirofumi; Otomo, Nao; Elcioglu, Nursel H.; Guo, Long (Wiley, 2019)
Dysosteosclerosis (DOS) is a distinct form of sclerosing bone disease characterized by irregular osteosclerosis and platyspondyly. DOS is genetically heterogeneous; however, only five cases with SLC29A3 mutations and a single case with a splice-site mutation of TNFRSF11A have been reported, and TNFRSF11A is also a causal gene for osteopetrosis, autosomal recessive 7 (OP-AR7). Thus, the causal genes of DOS and their genotype-phenotype associations remain unclear. In this study, we examined a Japanese patient with DOS and found a novel variant in TNFRSF11A. The homozygous variant was a G to T transversion at the first nucleotide of exon 9 (c.784G>T). Although the variant was predicted to cause a stop codon mutation (p.E262*), in silico evaluation of the exonic splicing elements followed by RT-PCR for the patient-derived cells showed that it caused aberrant splicing due to the change in the exonic splicing element and produced two types of aberrant transcripts: One caused a premature stop codon (p.E262Vfs*17) leading to nonsense mutation-mediated mRNA decay; the other produced a protein with interstitial deletion (p.E262_Q279del). The effects of the mutation on five splicing isoforms of TNFRSF11A were different from those in OP-AR7, but comparable with those in the first DOS with the TNFRSF11A mutation. Thus, we identified the second case of DOS caused by the TNFRSF11A splice-site mutation and confirmed the novel disease entity. (c) 2019 American Society for Bone and Mineral Research.
Keywords: RANK; MUTATION; ALTERNATIVE SPLICING; NONSENSE MUTATION-MEDIATED mRNA DECAY; OSTEOPETROSIS